Meningkatkan Kemampuan Guru dalam Menerapkan Model Pembelajaran Melalui Kegiatan Supervisi Pembelajaran Di SDN Gelang 03 Sumberbaru - Badri, Herul (Universitas Nusantara PGRI Kediri, 2021)
The gap between the ideal or what should be with reality or real conditions in the field in learning that should be in favor of student activities, meaningful for students, learning can be in the form of groups or individuals and teachers should not occur if teachers are able to design learning well through lesson plans . One of the causes of the teacher's condition is the lack of supervision by the principal, or even the lack of proper supervision by the principal. The objectives of this study are: (1) To determine the improvement of teachers' abilities in preparing lesson plans with learning models at SD Negeri Gelang 03 Sumberbaru Jember in the 2018-2019 academic year semester 2; (2) To find out the increase in the ability of teachers to apply learning models at SD Negeri Gelang 03 Sumberbaru Jember in the 2018-2019 academic year semester 2. The research subjects were SDN Bracelet 03 Sumberbaru Jember teachers in the Academic Year 2017/2018 with a total of 8 teachers teaching. This research model is an action research with two cycles. Methods of data collection is done by using observation and documentation. The results of the research can be concluded that: (1) Supervision of learning can improve the ability of teachers at SD Negeri Gelang 03 Jember in the 2018-2019 Academic Year in preparing lesson plans, this result can be seen from the percentage of success that increases from cycle to cycle.